Light Come Shining : the Transformations of Bob Dylan. - McCarron, Andrew PhD (Inner lives., 2016)
In this new biography of Bob Dylan, writer Andrew McCarron provides a unique look at Dylan's life and work by focusing on his various reinventions and incarnations.